Snoopy's grand adventure - Activision (Firm) (Los Angeles, CA Activision Inc., 2015)
Help Snoopy find Charlie Brown and his friends. Woodstock helps Snoopy in two player mode! Explore the far away places of Snoopy's imagination!
Title from disc label.
2 players, co-op 2.
ESRB rating: E. Everyone (mild cartoon violence).
System requirements: Xbox One game console; up to 1 GB storage; optional online play requires broadband Internet connection and Microsoft account or paid Xbox Live subscription. 2 players, co-op 2.
105188
Keywords: Snoopy -- (Fictitious character) -- Juvenile software; Brown, Charlie -- (Fictitious character) -- Juvenile software; Video games; Xbox video games; Adventure games; Juvenile works; Software; Xbox One video games